Characterization and expression profiling of ATP-binding cassette transporter genes in the diamondback moth, Plutella xylostella (L.) - Qi, Weiping (BMC Genomics, 2016)
BACKGROUND: ATP-binding cassette (ABC) transporters are one of the major transmembrane protein families found in all organisms and play important roles in transporting a variety of compounds across intra and extra cellular membranes. In some species, ABC transporters may be involved in the detoxification of substances such as insecticides. The diamondback moth, Plutella xylostella (L.), a destructive pest of cruciferous crops worldwide, is an important species to study as it is resistant to many types of insecticides as well as biological control Bacillus thuringiensis toxins. RESULTS: A total of 82 ABC genes were identified from our published P. xylostella genome, and grouped into eight subfamilies (ABCA-H) based on phylogenetic analysis. Genes of subfamilies ABCA, ABCC and ABCH were found to be expanded in P. xylostella compared with those in Bombyx mori, Manduca sexta, Heliconius melpomene, Danaus plexippus, Drosophila melanogaster, Tetranychus urticae and Homo sapiens. Phylogenetic analysis indicated that many of the ABC transporters in P. xylostella are orthologous to the well-studied ABC transporter genes in the seven other species. Transcriptome- and qRT-PCR-based analysis elucidated physiological effects of ABC gene expressions of P. xylostella which were developmental stage- and tissue-specific as well as being affected by whether or not the insects were from an insecticide-resistant strain. Two ABCC and one ABCA genes were preferentially expressed in midgut of the 4th-instar larvae of a susceptible strain (Fuzhou-S) suggesting their potential roles in metabolizing plant defensive chemicals. Most of the highly expressed genes in insecticide-resistant strains were also predominantly expressed in the tissues of Malpighian tubules and midgut. CONCLUSIONS: This is the most comprehensive study on identification, characterization and expression profiling of ABC transporter genes in P. xylostella to date. The diversified features and expression patterns of this gene family may be associated with the evolutionary capacity of this species to develop resistance to a wide range of insecticides and biological toxins. Our findings provide a solid foundation for future functional studies on specific ABC transporter genes in P. xylostella, and for further understanding of their physiological roles and regulatory pathways in insecticide resistance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-3096-1) contains supplementary material, which is available to authorized users.